Study and Evaluation of Stored Drinking Water Characteristics Using Three Types of Roof Water Tanks in Kirkuk Governorate, Iraq - Abdulkhaleq K Mahmood; Ali A Kamal; Ako R Hama (Wasit Journal of Engineering Sciences)
The scarcity of safe drinking water is one of the problems faced by the majority of cities in the world. Kirkuk city is one of these cities, which suffer from a shortage of drinking water. People have adopted the use of different rooftop tanks to overcome this problem. This research focuses on studying the effect of storage time on the five main characteristics of drinking water, which include, acid index (pH), electrical conductivity (EC), total suspended solids (TSS), total dissolved solids (TDS), and turbidity (Tr). Three types of tanks were used predominantly (galvanized metal, plastic, and aluminum tanks). By analyzing the results, the characteristics of three samples of municipal source water obtained. Three samples were taken from each tank at different periods (4, 8, and 12 days). The results showed that the storage time affected the characteristics of drinking water. These characteristics differed from one tank to another. Metal tanks showed an increase in total dissolved solids, due to the evaporation process, even as plastic and aluminum tanks showed an increase in pH. The properties of all storage water tanks changed with times, but overall, the results were within the Iraqi limitation for drinking water. It was not easy to only depend on the results of this study to believe that any one type of water tank was better than the other, as the values of most of the variables studied had varied from one type to other. However, many studies have indicated a number of health risks, and most significantly with regard to plastic tanks, which are said to contain dangerous organic compounds that can be transferred to water. Metal tanks can cause zinc leakage, caused by a number of environmental factors at high levels. Aluminum tanks also can have an effect on the water in tanks.